Association of the triglyceride-glucose index and vascular target organ damage in a Beijing community-based population - Ji, Wenjun; Gao, Lan; Sun, Pengfei; Jia, Jia; Li, Jianping; Wang, Xingang; Fan, Fangfang; Zhang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective: We aimed to explore the association between the triglyceride-glucose (TyG) index, a marker of insulin resistance, and vascular target organ damage (TOD) in a Beijing community-based population, China. Methods: A total of 6015 participants from an atherosclerosis cohort survey performed in Shijingshan district in Beijing, China were included in our analysis. Vascular TOD, including carotid-femoral pulse wave velocity (cfPWV), brachial-ankle pulse wave velocity (baPWV), the urine albumin-to-creatinine ratio (UACR) were all evaluated. Results: The overall mean age of all the participants was 62.35 years, 3951 (65.69%) were female, and mean TyG index was 8.81. In univariable regression analyzes, an increased TyG index was associated with higher cfPWV, baPWV, lnUACR and higher risk of cfPWV ≥ 10m/s, baPWV ≥ 1800cm/s and UACR ≥ 30mg/g. Multivariable regression analyzes showed subjects with the TyG index in top tertile had a significant increase in cfPWV (β = 0.29 m/s; 95% confidence interval [95% CI] 0.19-0.40; P for trend < 0.001), baPWV (β = 69.28 cm/s; 95%CI 50.97-87.59; P for trend < 0.001), lnUACR (β = 0.23; 95%CI 0.13-0.34; P for trend < 0.001), and had a higher risk of cfPWV ≥ 10m/s (odds ratio[OR] = 1.47; 95%CI 1.17-1.85; P for trend < 0.001), baPWV ≥ 1800cm/s (OR = 1.79; 95%CI 1.48-2.17; P for trend < 0.001) and UACR ≥ 30mg/g (OR = 1.71; 95%CI 1.30-2.24; P for trend < 0.001) after fully adjusting for age, sex, BMI, SBP, DBP, HDL-C, LDL-C, eGFR, self-reported CHD and stroke, antihypertensive drugs, hypoglycemic drugs, and lipid-lowering drugs. Consistent conclusions were obtained in the subgroups without hypoglycemic and lipid-lowering medications or aged younger than 65 years old. Conclusions: TyG index was positively associated with artery stiffness and nephric microvascular damage in a Beijing community-based population in China. This result provides evidence that TyG index may serve as a simple and effective indicator to reflect vascular TOD.